A randomized prospective study of the immediate outcomes of the use of a hydro-jet dissector and an ultrasonic surgical aspirator for laparoscopic liver resection. Issue 9 (September 2021) - Efanov, Mikhail; Kazakov, Ivan; Alikhanov, Ruslan; Vankovich, Andrey; Koroleva, Anna; Kovalenko, Dmitry; Salimgereeva, Diana; Tsvirkun, Victor; Khatkov, Igor
Abstract: Background: No prospective randomized trials comparing transection techniques for the liver parenchyma transection during laparoscopic liver resection have been performed. The aim of the study was to compare the immediate outcomes of hydro-jet dissection with ultrasonic surgical aspirator in laparoscopic liver parenchyma transection in a prospective randomized single-center study. Methods: Consecutive patients with liver benign and malignant tumors presenting to a single center from May 2017 to May 2020 were enrolled in the study. The primary endpoint was the intraoperative estimated blood loss. The secondary endpoints included duration of parenchymal transection, morbidity, and overall hospital stay. Results: A total of 68 patients were enrolled in the study, with 34 patients in each group. There were no differences between groups in the difficulty of resection (according to IWATE criteria and IMM score) and other basic surgical parameters. No differences were found in all primary and secondary endpoints except the expenditure. The cost of equipment was significantly higher in the group of ultrasonic aspirator. Conclusion: Despite the wider use of the ultrasonic aspirator in laparoscopic liver surgery, hydro-jet and ultrasonic surgical aspirators have shown similar efficacy and safety for transection of the liver parenchyma during laparoscopic resection.